If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6r + -11r + 4 = -47 Reorder the terms: 4 + -6r + -11r = -47 Combine like terms: -6r + -11r = -17r 4 + -17r = -47 Solving 4 + -17r = -47 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -17r = -47 + -4 Combine like terms: 4 + -4 = 0 0 + -17r = -47 + -4 -17r = -47 + -4 Combine like terms: -47 + -4 = -51 -17r = -51 Divide each side by '-17'. r = 3 Simplifying r = 3
| 4x+11=10x-1 | | 2x/5-x=x/15-4/3 | | 3x-3=-4x+32 | | 7x/11=5x/9+8 | | 3(v-3)-8v=1 | | 72=27+5x | | 18=-16t^2+35t-5.5 | | 4x^3-11x+5=0 | | 6(u+3)-8u=12 | | x(x+5)=20 | | -32=-6y+2(y-4) | | 8+40.8t-16t^2=10 | | -32=-6+2y(y-4) | | -7n-2=-48 | | (58x+65y)+(-9x+45y)= | | m(v-u)=I | | -18=5(x-6)-7v | | 5x+-3x=14 | | 36=4(y+6)-6y | | x+2+z=4 | | -21=-7x+2(x-3) | | 3x^2-70x+280=0 | | g/5=-16 | | 180=59 | | 7/5p+1/6p=3 | | a-17=-30 | | (-9x)-(6x)= | | 4+26/16+12+10+4= | | 5(-2n+4)=-10 | | 226-5x=40x+16 | | 4t^5(t-t^2+3t^3)= | | 12+4x=32 |